Gereja Menyikapi Radikalisme di Era Disruptif - Rahayu, Yohana Fajar; Utomo, Karyo; Arifianto, Yonatan Alex (Jurnal EFATA: Jurnal Teologi dan Pelayanan, 2023)
Church and radicalism; An attitude and the role of the church in an era of disruption amid a state of radicalism is to go hand in hand with the church's challenge to rise to light and love. The problem of radicalism is not only a local problem on a small scale but a problem being fought over by world leaders and the church. As part of human life, the church is called out from darkness to become light and as God's mandate amid the world, which naturally fulfills prophecy after prophecy regarding the end times. Where love grows cold, and man becomes selfish. Therefore the church is required to be able to play a role in helping the problem of radicalism by imitating the attitudes and examples of Jesus and his Apostles. For harmony and peace to be the goal of the church to have an impact using descriptive qualitative methods with a literature study approach and looking at the phenomenology of the church's situation in society, it can be concluded that the church exists to side with the truth and prioritize love, so the true church knows the meaning of the essence of the church as light and to be a blessing for humans because the existence of radicalism as a challenge to the church will bring the attitude and responsibility of the church to follow Jesus' example to fight with love and challenge the church in an era of disruption amid radicalism. Abstrak Gereja dan radikalisme; Sebuah sikap dan juga peran gereja dalam era disrupsi di tengah keadaan radikalisme adalah berjalan selaras dengan tantangan gereja untuk bangkit menjadi terang dan kasih. Permasalahan radikalisme bukan hanya menjadi masalah lokal dalam skala kecil, namun menjadi masalah yang digumulkan oleh pemimpin dunia dan gereja. Gereja sebagai bagian dari kehidupan manusia yang dipanggil keluar dari kegelapan untuk menjadi terang dan juga sebagai mandataris Tuhan di tengah dunia yang secara natural menggenapi nubuatan demi nubuatan terhadap akhir zaman. Di mana kasih menjadi dingin dan manusia akan mementingkan dirinya sendiri. Oleh karena itu gereja dituntut untuk dapat berperan dalam membantu masalah radikalisme dengan meneladani sikap dan teladan dari Yesus dan para Rasulnya. Supaya kerukunan dan kedamaian menjadi tujuan gereja berdampak menggunakan metode kualitatif deskriptif dengan pendekatan studi literatur dan melihat fenomenologi keadaan gereja ditengah masyarakat, dapat disimpulkan bahwa gereja hadir untuk berpihak kepada kebenaran dan mengutamakan kasih, maka gereja sejatinya mengetahui arti akan hakikat gereja sebagai terang dan menjadi berkat bagi manusia. Sebab adanya radikalisme sebagai tantangan gereja akan membawa sikap dan tanggung jawab gereja untuk mengikuti keteladanan Yesus memerangi dengan penuh kasih dan tantangan gereja dalam era disrupsi di tengah radikalisme.